Majority and minority the dynamics of race and ethnicity in American life - Yetman, Norman R. (Allyn and Bacon, 1999)
At long last, the revision of this widely respected reader is here The civil rights movement of the late 1960's originally shaped the approach of the first edition of "Majority and Minority, " and the indelible imprint of those events and the perspectives with which we approached them can be seen in each subsequent edition. Although many of the most contentious issues today differ from those of three decades ago, the persistence of racial and ethnic inequality and conflict has not diminished, but has remained deeply ingrained in American life. The concerns that undergirded the first edition of "Majority and Minority "remain as urgent today as in 1970. The book is divided into four major parts: 1) Introduction: Definitions and Perspectives, 2) Historical Perspectives, 3) Models of Ethnic Integration in the United States, and 4) The American People and the Future of Ethnicity. Each part is preceded by an introductory essay written by Yetman which discusses definitions, perspectives, and current issues in the field, while inter-relating and integrating the various articles within each section.